The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/chem.200500382
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Studies of the Conversion of 13C‐Labeled n‐Butane on Zeolite H‐ZSM‐5 by Using 13C Magic Angle Spinning NMR Spectroscopy and GC–MS Analysis

Abstract: By using 13C MAS NMR spectroscopy (MAS = magic angle spinning), the conversion of selectively 13C-labeled n-butane on zeolite H-ZSM-5 at 430-470 K has been demonstrated to proceed through two pathways: 1) scrambling of the selective 13C-label in the n-butane molecule, and 2) oligomerization-cracking and conjunct polymerization. The latter processes (2) produce isobutane and propane simultaneously with alkyl-substituted cyclopentenyl cations and condensed aromatic compounds. In situ 13C MAS NMR and complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
4
28
1
Order By: Relevance
“…However, ex situ GC-MS results exhibit formation of both unlabeled and double-labeled molecules in addition to single labeled i-butane after treating the sample at 293 K for 3 h, suggesting the possible bimolecular pathway although it is controversial because no propane and/or pentane appear in NMR spectra. The similar results are also found on H-MFI at 430-470 K. 106 Furthermore, the activation and skeletal arrangement of i-butane as a reverse reaction to View Online isomerisation of n-butane on SZ have been performed which shows that the isomerisation and its reverse reaction follow the same mechanism on the same catalyst under identical conditions. 107 It is also argued that the monomolecular mechanism of isomerisation is unfavorable in the case of n-butane.…”
Section: Isomerisation Of N-alkanessupporting
confidence: 77%
“…However, ex situ GC-MS results exhibit formation of both unlabeled and double-labeled molecules in addition to single labeled i-butane after treating the sample at 293 K for 3 h, suggesting the possible bimolecular pathway although it is controversial because no propane and/or pentane appear in NMR spectra. The similar results are also found on H-MFI at 430-470 K. 106 Furthermore, the activation and skeletal arrangement of i-butane as a reverse reaction to View Online isomerisation of n-butane on SZ have been performed which shows that the isomerisation and its reverse reaction follow the same mechanism on the same catalyst under identical conditions. 107 It is also argued that the monomolecular mechanism of isomerisation is unfavorable in the case of n-butane.…”
Section: Isomerisation Of N-alkanessupporting
confidence: 77%
“…As shown in Figure 1, besides methane, n-butane was also observed, as evidenced by the 13 CNMR signals at d = 26 (methylene group) and 14 ppm (methyl group). [14] Importantly,GC-MS analysis (Figure 1b-d) verified that the 13 C-labeled n-butane products could only have asingle 13 Clabel ([ 13 C 1 ]-nbutane,s ee also Table S1), thus indicating that the labeled n-butanes came from the 13 C-methylation of nonlabeled C 3 species.M eanwhile, the selective formation of [ 13 C 1 ]-nbutane rather than isobutane is in excellent agreement with those reported for propene methylation over acidic zeolites. [15] Thus,t he Scheme 2.…”
Section: Methodsmentioning
confidence: 92%
“…Normally, 1 H and/or 13 C NMR signal plots are continuously recorded versus reaction time for obtaining the kinetic parameters involving apparent rate constants and activation energies. Reaction kinetics from conventional 1 H and 13 C NMR are obtained by concentration variations of reactant or product in the bulk state, 153 however, the kinetics in a confined space such as a nanocage or nanochannel can not be achieved easily. It has been shown that the laserhyperpolarized (HP) 129 Xe NMR technique is powerful for the studying of porous materials.…”
Section: Reaction Kinetics In Heterogeneous Catalysismentioning
confidence: 99%